PARTNERSHIP ACTIVITY IN EFL READING CLASSROOM - Syarifah Dahliana (Universitas Islam Negeri Banda Aceh, 2016)
This paper analyzes the advantages of partnership activity in EFL reading classroom. Understanding a reading text may provide a challenge for some students as it involves a particular context and previous knowledge. For English as a foreign language (EFL) learners, the challenge becomes more complex as they need to understand the words and the written symbols of the foreign language and take the meaning of the sentence by making sense them with its context which may be unfamiliar to them. For this reason, choosing an activity that provides a wider opportunity for EFL students to share their thought and understanding of what they read as well as to listen others comprehension of the similar text is necessary in order to help the students have an accurate meaning of the text and learn how to be an effective reader. In this light, partnership activity is considered to be one of alternative ways to create an enjoyable and meaningful experience for EFL students to develop their reading skill of another language. The benefits of partnership activity include individual concerns and social life.